2022
DOI: 10.1136/ijgc-2021-003323
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable risk factors associated with long-term survival in women with serous ovarian cancer: a National Cancer Database study

Abstract: ObjectiveTo identify patient, clinical and hospital factors associated with long-term survival (≥10 years) in women with serous ovarian cancer.MethodsThis National Cancer Database cohort study included women with stage II–IV serous ovarian cancer. Multivariate logistic regression models were used to examine the association of long-term survival with patient (race, insurance, location, household income, education, distance traveled), clinical (age, comorbidities, stage, grade, primary treatment) and hospital fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…4 Certain unmodifiable disease-related factors have been shown to influence the prognosis of OC, thus, identifying preventive factors, especially modifiable ones, is a vital way to reduce morbidity and mortality for this disease. 5–7 Diet is a crucial modifiable prognostic factor that can be utilized to make suggestions for reducing OC mortality. Previous evidence has indicated that healthy components of a pre-diagnosis diet were associated with better OC survival, raising the possibility of healthy dietary choices after diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…4 Certain unmodifiable disease-related factors have been shown to influence the prognosis of OC, thus, identifying preventive factors, especially modifiable ones, is a vital way to reduce morbidity and mortality for this disease. 5–7 Diet is a crucial modifiable prognostic factor that can be utilized to make suggestions for reducing OC mortality. Previous evidence has indicated that healthy components of a pre-diagnosis diet were associated with better OC survival, raising the possibility of healthy dietary choices after diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified potential factors that affect the prognosis of OSC patients. For instance, Frost et al 20 reported that younger age and lower tumour stage and grade were associated with longer survival in OSC patients who survived for over 10 years. Similarly, Lisio et al 21 and Shim et al 22 identified older age at diagnosis, higher grade and stage as independent prognostic factors for poor prognosis in OSC patients.…”
Section: Discussionmentioning
confidence: 99%